Analisis Break Even Point sebagai Alat Perencanaan Laba pada CV Angin Mamiri Bitung - Rachman, Indah Nur Ainy; Alexander, Stanly W.; Latjandu, Lady Diana (Manajemen Bisnis dan Keuangan Korporat, 2024)
This research aims to analyze the break-even point as a profit planning tool at CV.Angin Mamiri Bitung. The type of research used is descriptive qualitative research. The data used are primary data collected through observation, interviews, and documentation methods. The results of the research indicate that the company has achieved sales above the break-even point, indicating that the company has generated profits in 2022 and 2023. Calculation of the break-even point assists in determining the margin of safety. The results for the margin of safety of CV. Angin Mamiri Bitung are within a safe limit, meaning that if the company experiences a decrease in sales volume, it will not have a significant impact if it remains above the calculated break-even point.